2014
DOI: 10.1161/jaha.113.000492
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A Increases Atherosclerosis in Pregnane X Receptor‐Humanized ApoE Deficient Mice

Abstract: BackgroundBisphenol A (BPA) is a base chemical used extensively in many consumer products. BPA has recently been associated with increased risk of cardiovascular disease (CVD) in multiple large‐scale human population studies, but the underlying mechanisms remain elusive. We previously reported that BPA activates the pregnane X receptor (PXR), which acts as a xenobiotic sensor to regulate xenobiotic metabolism and has pro‐atherogenic effects in animal models upon activation. Interestingly, BPA is a potent agoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 59 publications
2
70
1
Order By: Relevance
“…24 Expression of CD36 is enhanced by such pro-inflammatory cytokines as IL-1 (interleukin-1), IL-4 and IL-18, as well as M-CSF (macrophage colony-stimulating factor) and GM-CSF (granulocyte-macrophage colony-stimulating factor). [25][26][27][28][29] And increased concentration of proinflammatory cytokines leads to increased expression of CD36 on the surface of macrophages and stimulates the accumulation of ox-LDL. 21,24,30 CD36 expression is reduced by TGF-β (transforming growth factor beta) through phosphorylation of MAPK (mitogen-activated protein kinases), followed by phosphorylation of PPARγ and reduced gene transcription of CD36 in macrophages.…”
mentioning
confidence: 99%
“…24 Expression of CD36 is enhanced by such pro-inflammatory cytokines as IL-1 (interleukin-1), IL-4 and IL-18, as well as M-CSF (macrophage colony-stimulating factor) and GM-CSF (granulocyte-macrophage colony-stimulating factor). [25][26][27][28][29] And increased concentration of proinflammatory cytokines leads to increased expression of CD36 on the surface of macrophages and stimulates the accumulation of ox-LDL. 21,24,30 CD36 expression is reduced by TGF-β (transforming growth factor beta) through phosphorylation of MAPK (mitogen-activated protein kinases), followed by phosphorylation of PPARγ and reduced gene transcription of CD36 in macrophages.…”
mentioning
confidence: 99%
“…Therefore, in this study, the high dose of bisphenol A may exert proliferative activity on hFOB cells through the ER pathway. In addition, Sui et al [31] suggested a possible role of bisphenol A in cardiovascular disease in PXR-humanized apolipoprotein-deficient mice. Bisphenol A has also been reported to be the activator of the aryl hydrocarbon receptor (AhR) and SXR in hepatoma cells (HepG2) as well as in human hepatocytes [39].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, BPA is a potent agonist for human PXR but not for mouse or rat PXR [14]. To investigate the effects of BPA exposure on atherosclerosis development, a PXR-humanized ApoE deficient mouse model was generated [129]. Feeding study concluded that BPA increased atherosclerosis in ApoE −/− mice in a human PXR-dependent manner [129].…”
Section: Role Of Pxr In Regulating Atherosclerosis Development Andmentioning
confidence: 99%
“…To investigate the effects of BPA exposure on atherosclerosis development, a PXR-humanized ApoE deficient mouse model was generated [129]. Feeding study concluded that BPA increased atherosclerosis in ApoE −/− mice in a human PXR-dependent manner [129]. BPA-mediated human PXR activation also increased CD36 expression, lipid accumulation and foam cell formation in macrophages of PXR-humanized ApoE −/− deficient mice [129].…”
Section: Role Of Pxr In Regulating Atherosclerosis Development Andmentioning
confidence: 99%